MONETARY POLICY AND HERDING BEHAVIOR DEVELOPED MARKET AND EMERGING MARKET COMPARISON - Wibowo, Buddi (TRIKONOMIKA, 2021)
The research examines impact of monetary policy on herding behavior in the stock market. This study used OLS Regression, SUR, and Panel Regression Method. The results show that monetary policy affects herd behavior in stock market, specially in emerging market which have a specific characteristic such as low liquidity and low number of investor. Using SUR, this study show that common factors which affect the global herd behavior are not influential. Domestic stock market has its own variable that may initiate herd behavior.